PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PT. SINARMAS MULTIFINANCE CABANG SORONG - Emilia Dian Iriany; Andrey Maryen; Agnes Banea (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This research aims to determine the quality of service to customer satisfaction of PT.Sinarmas Multifinance which can be measured by :1. Tangibles , 2. Reliability, 3.Responsiveness 4.Asurance, 5.Emphaty. This research uses a quantitative research approach with an observation approach and the distribution of questionnaires ,with a sampel of 50 customers of PT.Sinarmas Multifinance Sorong City barnch. Using data analysis techniques : 1.simple linear regression analysis, 2. T test, 3.test the coefficient of determination (R2). The result of linear regression analysisi obtained the aquation Y = 5.675 + 0.695 X. where a =5.675 is a constant value,assuming that if the service increases by 1,there is an increase in customer satisfaction value of 0.695. The results of the analysis r^2 = 0.506 or 50.6%, which means that customer satisfaction is 50.6% influenced by the quality of service to customer of PT.Sinarmas Multifinance Sorong City branch ,while the remaining 49.4% is determinend by other variables not examinend in this study.